Identification of patients' rights to benefit from consumer health information services: A Delphi study - Hasan Ashrafi-rizi; Leila Shahrzadi; Zohreh Dehghani-Champiri (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Patients have different rights, one of which is their right to access health information. The aim of this study was to identify patients' rights to benefit from consumer health information services using a qualitative method. MATERIALS AND METHODS: The research method was qualitative using a Delphi technique. The statistical population consisted of 12 specialists in the field of medical library and information science and researchers and healthcare professionals. Eight dimensions and 42 items of patients' rights were identified and were approved by Delphi panel. RESULTS: Regarding patients' rights to benefit from consumer health information services, eight dimensions including the right to health knowledge, the right to access to health information, the professional behavior of medical librarians with patients, content richness, information seeking skills, awareness of new services and products, the ease of using health information centers, and the professional behavior of healthcare professionals with patients were identified and approved. CONCLUSION: Decreasing the gap between the health literacy of healthcare professionals and patients is one of the duties of medical librarians and health information professionals. Establishing of patient rights in the area of utilizing health information services is an important step in improving the quality of services received by patients.